INFLUENCE OF AN INTERNAL HEAT SOURCE ON THE TEMPERATURE FIELD OF FLAT SOLAR INSTALLATIONS (Archive of Conferences, 2022)
The results of studies on the calculation of the temperature field and heat fluxes through the translucent coatings of flat solar installations and the proposal of the corresponding expressions for determining their values are given.